Draft genome sequence of lactobacillus plantarum strains E2C2 and E2C5 isolated from human stool culture - Suryavanshi, Mangesh V.; Paul, Dhiraj; Doijad, Swapnil P.; Bhute, Shrikant S.; Hingamire, Tejashri B.; Gune, Rahul P.; Shouche, Yogesh S. (Standards in Genomic Sciences, 2017)
Probiotic Lactobacillus species offer various health benefits, thus have been employed in treatment and prevention of various diseases. Due to the differences in the isolation source and the site of action, most of the lactobacilli tested in-vitro for probiotics properties fail to extend similar effects in-vivo. Consequently, the search of autochthonous, efficacious and probably population specific probiotics is a high priority in the probiotics research. In this regards, whole genome sequencing of as many Lactobacillus as possible will help to deepen our understanding of biology and their health effects. Here, we provide the genomic insights of two coherent oxalic acid tolerant Lactobacillus species (E2C2 and E2C5) isolated from two different healthy human gut flora. These two isolates were found to have higher tolerance towards oxalic acid (300 mM sodium oxalate). The draft genome of strain E2C2 consists of 3,603,563 bp with 3289 protein-coding genes, 94 RNA genes, and 43.99% GC content, while E2C5 contained 3,615,168 bp, 3293 coding genes (93.4% of the total genes), 95 RNA genes and 43.97% GC content. Based on 16S rRNA gene sequence analysis followed by in silico DNA-DNA hybridization studies, both the strains were identified as Lactobacillus plantarum belonging to family Lactobacillaceae within the phylum Firmicutes. Both the strains were genomically identical, sharing 99.99% CDS that showed 112 SNPs. Both the strains also exhibited deconjugation activity for the bile salts while genome analysis revealed that the L. plantarum strains E2C2 and E2C5 also have the ability to produce vitamins, biotin, alpha-and beta-glucosidase suggesting potential probiotic activities of the isolates. The description presented here is based on the draft genomes of strains E2C2 and E2C5 which are submitted to GenBank under the accession numbers LSST00000000.1 and LTCD00000000.1, respectively.

Antitumor effects of Ir(III)-2H-indazole complexes for triple negative breast cancer - Panchangam, Rajeeva Lochana; Rao, Ramdas Nishanth; Balamurali, Musuvathi Motilal; Hingamire, Tejashri B.; Shanmugam, Dhanasekaran; Manickam, Venkatraman; Chanda, Kaushik (Inorganic Chemistry, 2021)
In this work, we have synthesized a series of novel C,N-cyclometalated 2H-indazole-ruthenium(II) and -iridium(III) complexes with varying substituents (H, CH3, isopropyl, and CF3) in the R4 position of the phenyl ring of the 2H-indazole chelating ligand. All of the complexes were characterized by 1H, 13C, high-resolution mass spectrometry, and elemental analysis. The methyl-substituted 2H-indazole-Ir(III) complex was further characterized by single-crystal X-ray analysis. The cytotoxic activity of new ruthenium(II) and iridium(III) compounds has been evaluated in a panel of triple negative breast cancer (TNBC) cell lines (MDA-MB-231 and MDA-MB-468) and colon cancer cell line HCT-116 to investigate their structure–activity relationships. Most of these new complexes have shown appreciable activity, comparable to or significantly better than that of cisplatin in TNBC cell lines. R4 substitution of the phenyl ring of the 2H-indazole ligand with methyl and isopropyl substituents showed increased potency in ruthenium(II) and iridium(III) complexes compared to that of their parent compounds in all cell lines. These novel transition metal-based complexes exhibited high specificity toward cancer cells by inducing alterations in the metabolism and proliferation of cancer cells. In general, iridium complexes are more active than the corresponding ruthenium complexes. The new Ir(III)-2H-indazole complex with an isopropyl substituent induced mitochondrial damage by generating large amounts of reactive oxygen species (ROS), which triggered mitochondrion-mediated apoptosis in TNBC cell line MDA-MB-468. Moreover, this complex also induced G2/M phase cell cycle arrest and inhibited cellular migration of TNBC cells. Our findings reveal the key roles of the novel C–N-cyclometalated 2H-indazole-Ir(III) complex to specifically induce toxicity in cancer cell lines through contributing effects of ROS-induced mitochondrial disruption along with chromosomal and mitochondrial DNA target inhibition.